Penalty-based nonlinear solver for optimal reactive power dispatch with discrete controls - Soler, Edilaine Martins [UNESP]; Asada, Eduardo N.; Da Costa, Geraldo R. M. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
The optimal reactive dispatch problem is a nonlinear programming problem containing continuous and discrete control variables. Owing to the difficulty caused by discrete variables, this problem is usually solved assuming all variables as continuous variables, therefore the original discrete variables are rounded off to the closest discrete value. This approach may provide solutions far from optimal or even unfeasible solutions. This paper presents an efficient handling of discrete variables by penalty function so that the problem becomes continuous and differentiable. Simulations with the IEEE test systems were performed showing the efficiency of the proposed approach. © 1969-2012 IEEE.
Keywords: Interior-point method; nonlinear programming; optimal power flow; Continuous variables; Discrete control variables; Discrete variables; Nonlinear programming problem; Optimal power flows; Optimal reactive power dispatch; Reactive dispatch; Nonlinear programming; Optimization